Africanising Distributed Leadership in Environmental Education Curriculum Management - Nonkanyiso Pamella Shabalala; Mishack Gumbo (Southern African Journal of Environmental Education, 2023)
Distributed leadership (DL) is a collaborative leadership approach that involves sharing decision-making and responsibilities among multiple individuals or groups within an organisation or institution. In the context of environmental education (EE) curriculum management, DL holds signifi cant relevance and can bring several benefits to stakeholders. This article critically examines the concept of DL in EE curriculum management and argues for an Africanised approach. It is focused on but not limited to institutions of learning. Managing EE curricula shows minimal consideration of Africanised DL. Drawing on an African philosophy of ubuntu, the article argues that an Africanised approach to DL can better serve the needs of African communities and promote sustainability in the region. As a conceptual article, we explore relevant literature to advance the idea of DL from an African perspective. In an era of environmental crisis and degradation in South Africa and other parts of the continent, an Africanised DL on EE curriculum management has the potential to off er relevant solutions. The article concludes by refl ecting on the Africanisation of DL and making recommendations for implementing an Africanised approach to DL in EE curriculum management.